2005
DOI: 10.1002/lsm.20237
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of transepidermal skin clearing agent delivery using a 980 nm diode laser

Abstract: The use of an inexpensive diode laser can significantly enhance the delivery of topically applied glycerol for optical skin clearing. The laser use involves application of an absorption substrate onto the skin surface. Using carbon paper left no unwanted residue behind and is considered optimal for this purpose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 15 publications
1
46
0
Order By: Relevance
“…Therefore, Q-switched 1,064-nm Nd:YAG laser irradiation was able to decrease the mean change in reflectance by almost ninefold at 575 nm and eightfold at 615 nm. Stumpp et al [18] reported that by using 980-nm diode laser, they successfully improved the image depth of OCT by about 42%. In their study, some artificial absorption substrates were applied to hamster skin surface to increase light absorption to provide controllable ablation of the SC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, Q-switched 1,064-nm Nd:YAG laser irradiation was able to decrease the mean change in reflectance by almost ninefold at 575 nm and eightfold at 615 nm. Stumpp et al [18] reported that by using 980-nm diode laser, they successfully improved the image depth of OCT by about 42%. In their study, some artificial absorption substrates were applied to hamster skin surface to increase light absorption to provide controllable ablation of the SC.…”
Section: Discussionmentioning
confidence: 99%
“…As for the mechanism of light irradiation enhances penetration of drug, it has been reported that lasergenerated stress waves could transiently increase permeability of SC and the cell plasma membrane [3,23,24] or laser irradiation could produce sufficient skin heating to disrupt keratinocyte [3,17,18,25], all of which facilitate glycerol penetration into dermal skin to induce optical skin clearing. Figure 3 shows that the light irradiation is important for control of skin permeation whether it is absorbed by the superficial or deep tissue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Beside the chemical agents, a number of physical methods of surmounting the skin barrier are proposed to enhance the diffusion, including low-and high-intensity irradiation [130,158], fractional lamp [131,133] and laser [132] microablation, mechanical microperforation [137,138], ultrasonic (US) irradiation [134,135,159], electrophoresis [160], needleless injection [161], mechanical removal of the surface layer by means of abrasive paper [136], epidermal stripping [162], and microdermabrasion [163].…”
Section: Immersion Clearingmentioning
confidence: 99%
“…The measurements of reflection spectra before and after the exposure have shown that the radiation of Nd:YAG laser in the modes of Qmodulation and long pulses can induce the improvement of transepidermal penetration of OCA by 8-9 folds as compared to the intact skin [130]. In the other study Stumpp et al [158] used a diode laser, operating at the wavelength 980 nm for the rodent skin irradiation using artificially absorbing substrates on the surface. The laser radiation provided heating of the stratum corneum and caused the failure of the protective barrier function.…”
Section: Immersion Clearingmentioning
confidence: 99%